If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(v + -9) = -24 Reorder the terms: -2(-9 + v) = -24 (-9 * -2 + v * -2) = -24 (18 + -2v) = -24 Solving 18 + -2v = -24 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -2v = -24 + -18 Combine like terms: 18 + -18 = 0 0 + -2v = -24 + -18 -2v = -24 + -18 Combine like terms: -24 + -18 = -42 -2v = -42 Divide each side by '-2'. v = 21 Simplifying v = 21
| -5x-9x=-56 | | (4/7)x+(2/7)=-(6/7) | | -3+x=-11 | | 8x-6x-4x=3 | | -2t-12=0 | | .5z+4.7=5.2z | | X^6-63x^2-64=0 | | d+2d=1134 | | [5x]=50 | | 4w+40=380 | | 0.25x+0.05(2-x)=0.10(21) | | 130+5x= | | 0.16y+0.07(y+6000)=1340 | | 4x-30=4x-12 | | 1/2(9)-1/6(-7)*-8/9(5) | | y/4=-16 | | 3x^3-7x^2+12x-28=f(x) | | (3/4)k-(1/2)=(1/9) | | 3x-3/6+x+11/4=9 | | 0.5x-0.6=5.3 | | 3x^3-7x^2+12x-28=0 | | 6x=4-2y | | 5b-28=2b+8 | | [x]=49 | | 8x+7x=14x | | 3x/8+5x/4=13 | | -2x-(7/2)=(1/2) | | 13x-12x+1/2=x+3/6 | | (3m-2n^2)(2m^2+3n)= | | -3(t-4)-7= | | 8+6*20/22 | | -3/5(y-15)-1/6y |